2018
DOI: 10.3348/kjr.2018.19.5.859
|View full text |Cite
|
Sign up to set email alerts
|

Tree-in-Bud Pattern of Pulmonary Tuberculosis on Thin-Section CT: Pathological Implications

Abstract: The “tree-in-bud-pattern” of images on thin-section lung CT is defined by centrilobular branching structures that resemble a budding tree. We investigated the pathological basis of the tree-in-bud lesion by reviewing the pathological specimens of bronchograms of normal lungs and contract radiographs of the post-mortem lungs manifesting active pulmonary tuberculosis. The tree portion corresponds to the intralobular inflammatory bronchiole, while the bud portion represents filling of inflammatory substances with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
1
31
2
Order By: Relevance
“…Similarly, Lee et al [9] showed a representative case report of CMs in a patient with a minimal extent of disease and found that CMs presented as nodular aggregations of granulomas in the peribronchiolar interstitium. In contrast, when CMs were pathologically analyzed in patients with advanced TB disease, they corresponded to the aggregation of tree-in-bud lesions of impacted caseation material within the bronchioles and alveolar ducts [15]. The difference in pathologic nature of CMs between our series and previously reported cases [15] might come from the difference in the stage of TB infection.…”
Section: Plos Onecontrasting
confidence: 71%
See 3 more Smart Citations
“…Similarly, Lee et al [9] showed a representative case report of CMs in a patient with a minimal extent of disease and found that CMs presented as nodular aggregations of granulomas in the peribronchiolar interstitium. In contrast, when CMs were pathologically analyzed in patients with advanced TB disease, they corresponded to the aggregation of tree-in-bud lesions of impacted caseation material within the bronchioles and alveolar ducts [15]. The difference in pathologic nature of CMs between our series and previously reported cases [15] might come from the difference in the stage of TB infection.…”
Section: Plos Onecontrasting
confidence: 71%
“…In contrast, when CMs were pathologically analyzed in patients with advanced TB disease, they corresponded to the aggregation of tree-in-bud lesions of impacted caseation material within the bronchioles and alveolar ducts [15]. The difference in pathologic nature of CMs between our series and previously reported cases [15] might come from the difference in the stage of TB infection. All our cases were live subjects with an early stage, while the latter cases were a post-mortem lung in advanced stage.…”
Section: Plos Onecontrasting
confidence: 71%
See 2 more Smart Citations
“…*Corresponding Author 28 29 Adrie JC Steyn, Ph.D. 30 asteyn@uab.edu or adrie.steyn@ahri.org 31 +27-31-260-4715 32 33 34 35 Our current understanding of the pathophysiology of human pulmonary TB is limited by the paucity 38 of human TB lung tissue for study and reliance on 2D analytical methods. Here, to overcome the 39 limitations of conventional 2D histopathology, we used high-resolution 3D X-ray imaging 40 (µCT/nCT) to characterize necrotic lesions within human tuberculous lung tissues in relation to the 41 airways and vasculature.…”
mentioning
confidence: 99%